Effect of pulverisation on sulfide and tin antimonide anodes for sodium-ion batteries - Priyanka, P.; Nalini, B.; Soundarya, G. G.; Christopher Selvin, P.; Dutta, Dimple P. (Frontiers in Energy Research, 2023)
Metal sulfides and alloy anodes are a good choice for sodium-ion batteries (SIBs) since they have many benefitting advantages such as higher specific capacity, good cyclic stability, and higher rate capability. Tin antimony (Sn2Sb3), as an anode, exhibits a remarkable theoretical capacity of 753 mAhg−1 that has not been realized so far for reaching the theoretical capacity; pulverization of sulfide-based material [copper sulfide (CuS)] along with tin antimonide would be a better option for obtaining a high-performance anode for SIBs. Hence, an attempt is made to study the pulverisation effects of these two materials when employed as an anode for SIBs. The pulverised compound CuS: Sn2Sb3 delivers an initial discharge capacity of 659 mAhg−1 at 0.1 Ag−1 vs. Na/Na+ with high stability retaining up to 100% efficiency over 100 cycles. The present work highlights the structural changes upon pulverisation and its impact on delivering higher capacity.